Prevalence of Contraceptive Use and Different Factors Influencing its Choice among Women in Tehran, Iran - Fatemeh Karami; Fatemeh Gholami; Asemeh Ghasemi (Mashhad University of Medical Sciences, 2021)
Background and aim: Family planning has pivotal role in the improvement of various aspects of community health. Owing to the incomplete previously performed studies, the present research was carried out to measure the prevalence of contraceptive use and its key influencing factors among the women residing in Tehran.Methods: An analytical and observational cross-sectional study was performed on 395 women (18-40 years old) whom attended private clinics in three strict of Tehran determined through clustering sampling, during January to July 2019. A questionnaire including 24 questions was completed for all the participants. The questions were designed to determine the type of contraception and its influencing factors including demographic characteristics, attitude of women and their husbands as well as social, economic and cultural factors. The collected data were analyzed using SPSS software (version 22).Results: The overall rate of using contraception was 75.2% and traditional methods were the most prevalent contraception (55.9%). Frequency of the different contraceptive methods was meaningfully different among women with various age categories (P=0.01[l1] ). Housing location was meaningfully associated with no contraception (P=0.04), and except for withdrawal, house size (p <0.0001) and family income (P=0.007) were significantly associated with the type of contraception. Moreover, it was shown that the attitude of women and their husbands as well as the number of children significantly affected the contraception choice (p <0.0001).Conclusion:  High prevalence of withdrawal method even among highly educated women is relying on the demand for education programs, especially among couples who are seeking the least successful contraceptive methods.